Epidemiology Of Disability in Incident Leprosy Patients at Supervisory Urban Leprosy Unit of Nagpur City - Chavan, L B; Patel, Prakash (National Journal of Community Medicine, 2011)
Leprosy is a chronic infectious disease caused by Mycobacterium Leprae, affecting mainly peripheral nerves and skin. Disabilities and deformities are major concerns as it triggers social, economic and psychosocial problems of leprosy patients. In the study, 105 incident leprosy patients registered in a randomly selected Supervisory Urban Leprosy Unit during year 2004-05 were interviewed. Disability was graded as per WHO-2 point scale. There were 52 male and 53 female with median age of 26 years. The WHO grade -II disability was 12.38 % and it was significantly higher among manual workers and housewives (76.92%, P<0.05). Hands and feet disabilities were found in 38.10 % while nobody had eye related disability. Subjects with delayed diagnosis beyond 12 months had significantly higher grade-2 disabilities than diagnosed earlier (P<0.05). Disability rate was also higher in Multi-Bacillary leprosy patients (P<0.001). Ulcer was the most common type of grade-II deformity (61.54 %) which was significantly higher in females (P<0.05). Prevalence of disability was found higher in study area than national average. Awareness about Prevention Of Deformities (POD), early diagnosis (<12 months) and treatment are recommended to avert visible deformities and hence social stigma in leprosy patients.